Conflict, domination, and violence : episodes in Mexican social history - Illades, Carlos (Studies in Latin American and Spanish history, 2017)
"Conflict, Domination, Violence--in this wide-ranging, briskly narrated volume from acclaimed Mexican historian Carlos Illades, these three phenomena register the pulse of a diverse, but inequitable and discriminatory, social order. Drawing on rich and varied historical sources, Illades guides the reader through seven signal episodes in Mexican social history, from rebellions under Porfirio Díaz's dictatorship to the cycles of violence that have plagued the country's deep south to the recent emergence of neo-anarchist movements. Taken together, they comprise a mosaic history of power and resistance, with artisans, rural communities, revolutionaries, students, and ordinary people confronting the forces of domination and transforming Mexican society"--Provided by publisher.